2007
DOI: 10.1007/s00227-007-0752-7
|View full text |Cite
|
Sign up to set email alerts
|

A model of area fidelity, nomadism, and distribution patterns of loggerhead sea turtles (Caretta caretta) in the Mediterranean Sea

Abstract: Sea turtle tagging carried out in Italy in the period 1981-2006 resulted in 125 re-encounters of loggerhead turtles (Caretta caretta) after a mean of 2.5 years, from different marine areas in the Mediterranean. At first finding, turtles ranged 25-83 cm of curved carapace length. Data were analyzed according to size, area, habitat type, season, in order to provide indication of movement patterns. When integrated with other information, results indicate that: (1) a part of turtles in the oceanic stage show a nom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 27 publications
7
64
0
Order By: Relevance
“…A degree of permanence in the same area was indicated by tag returns in the western and eastern Mediterranean (Casale et al 2007a), and was directly observed through satellite tracking in some cases in the western Mediterranean (Revelles et al 2007a) but not in others, either in the western (Cardona et al 2005;Eckert et al 2008;Cardona et al 2009) or in the eastern Mediterranean (Bentivegna 2002). In general, resident areas of juveniles in oceanic zones are much wider than in neritic zones (Revelles et al 2007b;Cardona et al 2009;Casale et al 2012aCasale et al , 2012b (Figure 4), as also observed for adults in the Mediterranean and elsewhere (Hawkes et al 2006;Schofield et al 2010a).…”
Section: Large Juvenilesmentioning
confidence: 89%
See 3 more Smart Citations
“…A degree of permanence in the same area was indicated by tag returns in the western and eastern Mediterranean (Casale et al 2007a), and was directly observed through satellite tracking in some cases in the western Mediterranean (Revelles et al 2007a) but not in others, either in the western (Cardona et al 2005;Eckert et al 2008;Cardona et al 2009) or in the eastern Mediterranean (Bentivegna 2002). In general, resident areas of juveniles in oceanic zones are much wider than in neritic zones (Revelles et al 2007b;Cardona et al 2009;Casale et al 2012aCasale et al , 2012b (Figure 4), as also observed for adults in the Mediterranean and elsewhere (Hawkes et al 2006;Schofield et al 2010a).…”
Section: Large Juvenilesmentioning
confidence: 89%
“…In any case, such a capturemark-recapture method has provided basic but most useful information on the movement patterns and migrations of many sea turtle populations (e.g. Meylan 1982) including Mediterranean ones (Margaritoulis et al 2003;Casale et al 2007a). …”
Section: Methods For Studying Sea Turtle Movementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The northern Adriatic is an important foraging area for adults from Greek (Lazar et al 2004, Carreras et al 2006, Giovannotti et al 2010, Garofalo et al 2013 and Turkish rookeries, as well as for juveniles (Casale et al 2004). Other important areas are the southern Adriatic (Casale et al 2012a), the Ionian Sea, the Strait of Sicily, and the Tunisian shelf (Margaritoulis et al 2003, Casale et al 2007b, Casale et al 2014). The latter is frequented by turtles from Greek rookeries, Libya, and the Atlantic (Garofalo et al 2013).…”
Section: Sea Turtle Distributionmentioning
confidence: 99%